2017
DOI: 10.1002/open.201700080
|View full text |Cite
|
Sign up to set email alerts
|

Silica Mineralization of DNA‐Inspired 1D and 2D Supramolecular Polymers

Abstract: The preparation of hybrid materials from supramolecular polymers through the sol‐gel process is presented. Supramolecular polymers are assembled from phosphodiester‐linked pyrene oligomers and act as water‐soluble one‐ or two‐dimensional templates for silicification. The fibrillary and planar morphologies of the assemblies, as well as the excitonic interactions between the chromophores, remain unaffected by the silicification process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…1, can be used as templates for the growth of inorganic materials. [23] We demonstrated that using water-soluble 2D scaffolds opens the door to nanothin silicates. First, a positively charged reagent, methyl [3-(trimethoxysilyl)propyl] ammoniumchloride, is added to create nucleation sites on the nanosheet surface.…”
Section: D Motifs In Tubular Systemsmentioning
confidence: 93%
See 1 more Smart Citation
“…1, can be used as templates for the growth of inorganic materials. [23] We demonstrated that using water-soluble 2D scaffolds opens the door to nanothin silicates. First, a positively charged reagent, methyl [3-(trimethoxysilyl)propyl] ammoniumchloride, is added to create nucleation sites on the nanosheet surface.…”
Section: D Motifs In Tubular Systemsmentioning
confidence: 93%
“…TEM images of nanosheets from 1 before (A, B) and after (C, D) growing a silica shell around the SP sheets (adapted from ref. [23]). Reprinted with permission; copyright Wiley.…”
Section: From 2d Supramolecular Polymers To 2d Covalent Materialsmentioning
confidence: 99%
“…Thus, replacing the two amide groups of the pyrene core with triple bonds leads to the formation of micrometre long fibers even with very short oligomers, such as trimer 20 and at considerably lower ionic strength. 27 The enhanced tendency to aggregate was ascribed to an increased hydrophobicity of the alkynyl linkers relative to carboxamides. Owing to the dynamic nature of supramolecular polymers, oligomers 21 and 22 are readily integrated into fibers by cooling a pre-heated mixture (above the temperature of disassembly) containing both types of oligomers.…”
Section: One-dimensional Supramolecular Systemsmentioning
confidence: 99%
“…Due to the multi-charged nature of the nanosheets in an aqueous environment, it is possible to use them as nucleation templates for biomineralization. 27 In this approach, a shell of various inorganic materials with a controlled thickness can be grown at the outside of a template. Once oligophosphodiester derived nanosheets are formed, 2D silica sheets can be prepared by adapting the protocols previously developed and successfully applied to long double-stranded DNAs (Fig.…”
Section: Two-dimensional Supramolecular Assembliesmentioning
confidence: 99%
“…115 Adding the complements to the DNA gives networks-of-ribbons, presumed to occur through blunt-end stacking. 116 Interface with other nanomaterials is also possible: gold nanoparticles with complementary DNA attached can hybridise to these ribbons, 117 while silica mineralisation can also be achieved on oligopyrenotide nanostructures 118 and cationic porphyrins can bind to them as 'groove binders.' 119 Li and coworkers have also extended their DNA scaffolded chromophores to non-nucleosidic systems which combine selfassembly with unusual optical properties.…”
Section: Sequence Defined Non-nucleosidic Polymers For Emerging Functmentioning
confidence: 99%